ANALYTICAL APPROACHES OF ACCOUNT MANAGEMENT ON ENTERPRISE (Economic journal of Lesya Ukrainka Volyn National University, 2018)
In this study, the theoretical and practical questions of the analysis process in the profit management system at the enterprise are described. The analysis carried out during the research allows us to conclude that the value of profit is the final reflection of the financial result. The influence on the profit of the system of factors of the dependent and independent of the efforts of the enterprise is found out; systematic theoretical and methodological approaches to profit management at the enterprise; the motivation mechanism for managing measures to maximize profits is proposed; The conceptualization ofthe scheme of analytical behavior of subjects (users) of financial information is outlined; recommendations were made to achieve higher financial results of the enterprise.
Keywords: profit, net profit, equity, analysis of production activity, liquidity, cost